Computers Learn to Listen, and Some Talk Back - Horvitz, Eric (The New York Times | Science | Smarter Thank You Think, 2010)
Smarter Than You Think: Articles in this series will examine the recent advances in artificial intelligence and robotics and their potential impact on society.